Barriers to the Formalization of Partnerships between TBM Komunitas Gada Membaca and MIS Winduraja in Digital Literacy Programs - Lestari, Widia; Lusiana, Elnovani; Prahatmaja, Nurmaya (Journal of Innovative and Creativity, 2026)
The study purpose was to identify the factors inhibiting the formalization of the partnership between TBM Komunitas Gada Membaca and MIS Winduraja, as the existing collaboration remains informal despite its important role in supporting digital literacy programs. Materials and methods. This study employed a qualitative case study approach. Data were collected through in-depth interviews, observation, and literature review involving three purposively selected informants. Data analysis was conducted interactively through the stages of data reduction, data display, and the formulation as well as verification of conclusions. Results. The findings indicate that the barriers to formalization arise from several key factors. First, the dominance of trust-based relational governance encourages reliance on informal coordination without clear documentation of roles and responsibilities. Second, the strong focus on program implementation prioritizes immediate impact over administrative processes such as monitoring, evaluation, and reporting. Third, limited administrative capacity, particularly due to dependence on volunteers, hinders the preparation of formal agreements and systematic documentation. Fourth, the low perceived urgency of formalization, influenced by operating under the same institutional foundation, reduces the need for formal contracts. Lastly, formalization tends to occur only when triggered by external demands, such as funding or reporting requirements, rather than through proactive planning. Conclusion. The barriers are multidimensional, involving structural, organizational, and relational aspects. Future research should explore hybrid governance models to strengthen sustainable literacy partnerships.